Releasing jobs for the young? Early retirement and youth unemployment in the United Kingdom - James Banks; Richard Blundell; Antoine Bozio; Carl Emmerson (Institute for Fiscal Studies (IFS), 2010)
This paper tries to assess whether or not we have any empirical evidence of links between early retirement and youth unemployment. Most economists would today dismiss the idea immediately as another version of the naive 'lump-of-labor fallacy'. In its most basic form, this proposition holds that there is a fixed supply of jobs and that any reduction in labor supply will reduce unemployment by offering jobs to those who are looking for ones. Taken to the extreme, this view would support that the idea that a high level of employment of one group of individuals can only be at the expense of another group: if for instance were the population of a country to increase, younger individuals would be unemployed as older individuals would not 'release' enough jobs for the new entrants. The absurdity of this view in the long term is simply seen by considering the fact that the size of a country does not bear any relation to the share of population unemployed.
Keywords: 330; Flexible Altersgrenze; Beschäftigungseffekt; Jugendliche Arbeitskräfte; Jugendarbeitslosigkeit; Rentenreform; Großbritannien